2010
DOI: 10.1097/ncc.0b013e3181bb0cf1
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Views of Surgery and Surveillance for Familial Adenomatous Polyposis

Abstract: One important aspect of living with FAP shared by the participants concerned ways of managing life concerns, something that healthcare providers caring for patients with FAP should identify and support. Furthermore, continuity of care by health care providers with good knowledge about FAP can be an important way of reducing patient concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…If FAP is not treated, it develops into colorectal cancer that occurs in 100% of cases by the age of 50 years (Greco, 2007;Razmus et al, 2008). Prophylactic surgery (removal of the entire large bowel) is recommended by the age of 18-20 years and regular gastroscopy is also recommended postoperatively to detect development of polyps in the duodenum (Fritzell, Persson, Bjork, Hultcrantz, & Wettergren, 2010). Those with a genetic predisposition to FAP are also at risk of developing cancers of the thyroid, small bowel, liver, pancreas, and brain (Greco, 2007).…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%
“…If FAP is not treated, it develops into colorectal cancer that occurs in 100% of cases by the age of 50 years (Greco, 2007;Razmus et al, 2008). Prophylactic surgery (removal of the entire large bowel) is recommended by the age of 18-20 years and regular gastroscopy is also recommended postoperatively to detect development of polyps in the duodenum (Fritzell, Persson, Bjork, Hultcrantz, & Wettergren, 2010). Those with a genetic predisposition to FAP are also at risk of developing cancers of the thyroid, small bowel, liver, pancreas, and brain (Greco, 2007).…”
Section: Familial Adenomatous Polyposismentioning
confidence: 99%
“…4,[6][7][8][9] To explore patients' views of what it is like to live with FAP, our research group conducted focus-group interviews among patients who had undergone prophylactic colorectal surgery. 5 The results showed that abdominal discomfort and pain were important reasons for concern in regard to living with FAP, including insecurity caused…”
Section: Introductionmentioning
confidence: 99%
“…Most patients also report a need for dietary restrictions 3,4 to avoid disturbing abdominal symptoms. 5 Symptoms have been suggested to be more prevalent in patients with an IPAA than in those with an IRA; 3 knowledge is limited regarding symptoms experienced by patients with an ileostomy. 6 As measured with standardized questionnaires, health status in patients with FAP after prophylactic colorectal surgery has been reported to be equivalent to population norms.…”
Section: Introductionmentioning
confidence: 99%
“…Here again there is a stark difference between BRCA and FAP. Without surgical intervention, mortality from gastrointestinal cancer for individuals with FAP is almost 100%, with half of patients dying before age 50 [4]. In contrast, individuals with a BRCA mutation who do not have prophylactic surgery can have a normal, or near normal, life expectancy [13].…”
Section: Genetic Penetrance and Mortalitymentioning
confidence: 99%
“…Most hereditary cancers have established prophylactic treatments that are routinely recommended by health care professionals. For example, the standard of care for individuals with gene alterations related to FAP is a prophylactic colectomy between 18 and 20 years old [4]. While there is a standard of care for BRCA positive women, it pertains only to their ovarian cancer risk: surveillance for ovarian cancer has proven ineffective [5], so the consensus is that oophorectomy should be offered to all women carrying a BRCA mutation between age 35-40 or once childbearing is complete [3].…”
Section: The Medical Factors No Standard Of Carementioning
confidence: 99%